Modeling the Process of Information Encountering Based on the Analysis of Secondary Data - Jiang, Tingting; Fu, Shiting; Guo, Qian; Song, Enmei (Information in Contemporary Society, 2019)
The critical incident technique (CIT) has been applied extensively in the research on information encountering (IE), and abundant IE incident descriptions have been accumulated in the literature. This study used these descriptions as secondary data for the purpose of creating a general model of IE process. The grounded theory approach was employed to systematically analyze the 279 IE incident descriptions extracted from 14 IE studies published since 1995. 230 conceptual labels, 33 subcategories, and 9 categories were created during the data analysis process, which led to one core category, i.e. “IE process”. A general IE process model was established as a result to demonstrate the relationships among the major components, including environments, foreground activities, stimuli, reactions, examination of information content, interaction with encountered information, valuable outcomes, and emotional states before/after encountering. This study not only enriches the understanding of IE as a universal information phenomenon, but also shows methodological significance by making use of secondary data to lower cost, enlarge sample size, and diversify data sources.